Activities of red clover (Trifolium pratense L) as antiosteoporosis - Istiqamah, Istiqamah (Maliki Interdisciplinary Journal, 2024)
Osteoporosis is a disease characterized by decreased bone mass and abnormalities in the microarchitecture of bone tissue, which leads to decreased bone strength, increased bone fragility, and even an increased risk of fractures. The aim of this study was to find out the benefits of red clover (Trifolium pratense L.) as an alternative anti-osteoporosis medicine. The study was conducted using a quantitative approach combined with a literature review method. In this approach, researchers collect information on the topic and analyze the results of studies from the sources as a reference for the study. The results of the study showed that red clover contains phytoestrogens that help reduce the activity of the osteoclastogenesis process and bone resorption, increase osteoblastogenesis and the process of bone formation, and therefore can slow down the progression of osteoporosis.